Sports injuries in wheelchair rugby - A pilot study - Bauerfeind, J.; Koper, M.; Wieczorek, J.; Urbanski, P.; Tasiemski, T. (Journal of Human Kinetics, 2015)
The aim of the study was to analyze etiology and the incidence of sports injuries among wheelchair rugby players. Moreover, we verified if the levels of aggressiveness and anger presented by the athletes and their roles in the team influenced the incidence and severity of the injuries. The study involved 14 male players, members of the Polish National Wheelchair Rugby Team. During a 9-month period, the athletes participated in up to 9 training camps and 4 Wheelchair Rugby tournaments. The study was based on the Competitive Aggressiveness and Anger Scale, registry of sports injuries consulted and non-consulted with a physician and a demographic questionnaire. The following observations were made during the 9-month period corresponding to a mean of 25 training and tournament days: 1) wheelchair rugby players experienced primarily minor injuries (n=102) that did not require a medical intervention, 2) only four injuries needed to be consulted by a physician, 3) sports injuries occurred more frequently among offensive players than in defensive players, 4) offensive players showed a tendency to higher levels of anger and aggressiveness than defensive players. It can be concluded that wheelchair rugby is a discipline associated with a high incidence of minor injuries that do not require a medical intervention. The incidence rate of injuries during the analyzed period was 0.3 per athlete per training day.